Revitalisasi Produk Lokal Menuju Andalan Daerah Musi Rawas: Pendekatan Kesejahteraan dan Dodeca-Helix - Fadlu Robby; Sri Lastuti; Mulyani Puji Lestari; Meilia Susanti; Reza Septian; Hendri Reza Fahlepi; Roby; Yuyun Suwanti; Masrurah; Huzaima Yentriani; M. Solihin; Romasta Napitupulu; Melisa Afrianti; Naily Maimanah; Andriyanto Aditama; Jalin Elsaprike; Herie Saksono (Jurnal Bina Praja, 2025)
This study aims to formulate a revitalization model for Regional Flagship Products (PLUD) into Regional Flagship Products (RFP) in Musi Rawas Regency, by integrating the Wellbeing Methodology and the Dodeca-Helix collaboration ecosystem. The revocation of the Minister of Home Affairs Regulation Number 9 of 2014 has created a regulatory vacuum, requiring local governments to proactively formulate policies grounded in empirical evidence. Through a mixed-methods approach, primary data were collected from 885 representative respondents. Evaluation was conducted using the Perception, Participation, and Acceptability Index (PPA) and Multi-Criteria Decision Analysis (MCDA). The results showed that the MR-RFP Feasibility Index was at 5.67 (moderate category). A “High Readiness, Low Literacy Paradox” was observed, in which community enthusiasm is very high but conceptual understanding of innovation, governance, and financial literacy remains low. Aspiration analysis reveals a dualism in economic vision: palm oil and rice represent commodity stability, while coffee, culinary arts, and batik represent the experience economy. Based on MCDA, Padi Dayang Rindu and Kopi Selangit are designated as the main flagship candidates due to their superior geographical indications, with palm oil downstreaming as a strategic supporting product. Ten public strategic imperatives absolutely demand a shift in government and regional government intervention from physical infrastructure development to providing software capacity in the form of digital marketing, branding, and improving human resource quality. This study recommends the institutionalization of an innovation ecosystem through the Dodeca-Helix model to orchestrate 12 stakeholders in realizing the Musi Rawas MANTAB 2025-2029 vision.